2020
DOI: 10.32607/actanaturae.11152
|View full text |Cite
|
Sign up to set email alerts
|

Palette of Luciferases: Natural Biotools for New Applications in Biomedicine

Abstract: Optoanalytical methods based on using genetically encoded bioluminescent enzymes,luciferases, allow one to obtain highly sensitive signals, are non-invasive, and require no external irradiation. Bioluminescence is based on the chemical reaction of oxidation of a low-molecular-weight substrate (luciferin) by atmospheric oxygen, which is catalyzed by an enzyme (luciferase). Relaxation of the luciferin oxidation product from its excited state is accompanied by a release of a quantum of light, which can be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 94 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Potassium humate [61] Decrease of bioluminescence at concentration 0.5 g/L Isoflavonoids [62] High level of luciferase inhibition Divalent ions of various metals [63] Luminescence decrease in presence of Hg 2+…”
Section: Investigated Inhibitors [Reference] Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium humate [61] Decrease of bioluminescence at concentration 0.5 g/L Isoflavonoids [62] High level of luciferase inhibition Divalent ions of various metals [63] Luminescence decrease in presence of Hg 2+…”
Section: Investigated Inhibitors [Reference] Effectsmentioning
confidence: 99%
“…The effect of divalent ions on the bioluminescence of luciferase of fireflies has been established and it has been shown that an increase in the concentration of Mn 2+ , Ca 2+ or Mg 2+ ions does not affect the quantum yield and color of radiation, while the presence of Zn 2+ , Cd 2+ , Fe 2+ , Ni 2+ and Co 2+ ions cause a bathochromic shift, and luminescence decreased sharply in the presence of Hg 2+ [63].…”
Section: Investigated Inhibitors [Reference] Effectsmentioning
confidence: 99%
“…Ten luciferins have been identified in bioluminescent organisms, along with several corresponding luciferases [3]. Firefly D-luciferin, coelenterazine, Cypridina luciferin, and their derivatives have been commercialized, and are primarily used in reporter assays, in vivo and in vitro imaging, and immunoassay [4][5][6][7][8][9]. Several companies, such as Promega and Toyobo, have also commercialized luciferase genes.…”
Section: Introduction: Why Do We Have To Quantify the Optical Signal?mentioning
confidence: 99%
“…The brightness, thermostability, and small size of reporter proteins make them useful in applications. Their small size can reduce steric hindrance and misfolding of reporter‐fused proteins [3,4], making them amenable to genome insertion [5] and drug screening [6]. Additionally, the use of small luciferases can yield higher signals in bioluminescence resonance energy transfer (BRET)‐based assays [7].…”
Section: Introductionmentioning
confidence: 99%